Metal support body of solid oxide fuel cell and preparation method of metal support body
By adding nickel, cobalt, molybdenum and other additives to the 400 series stainless steel metal powder, and using casting molding and multi-layer stacking isostatic pressing processes, a porous metal support with high porosity and high conductivity was prepared, which solved the problem of current There are problems with poor antioxidant performance in the technology, which improves battery performance and reduces costs.
Patent Information
- Application Number
- CN202411641615.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing metal-supported solid oxide fuel cells have poor oxidation resistance, resulting in increased resistance and poor conductivity, which leads to battery failure.
A mixed slurry consisting of 400 series stainless steel metal powder and additives such as nickel, cobalt, molybdenum, etc. is prepared by casting molding and multi-layer stacking isostatic pressure and sintering to prepare a porous metal support with high porosity and high conductivity. .
It significantly improves the oxidation resistance and conductivity of the metal support, reduces manufacturing costs, extends the service life of the battery, and improves the overall performance of the battery.
Smart Images

Figure CN119457083A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid oxide fuel cell, in particular to a solid oxide fuel cell metal support and a preparation method thereof. Background Art
[0002] Solid oxide fuel cells (SOFCs) can directly convert chemical energy into electrical energy, breaking through the limitations of the Carnot cycle of internal combustion engines, with high energy conversion efficiency (more than 60% power generation efficiency); diverse fuels, environmentally friendly, pollution-free (no noise, no NOx emissions), modular, and suitable for forming high-power battery stacks; all-solid structure, stable electrolyte materials, no corrosion to other battery components; wide range of uses, depending on the type of fuel can be used for portable power, combined heat and power, distributed energy (W-MW level). When running at high temperatures, the open circuit voltage of the battery is close to the theoretical electromotive force, and the ohmic resistance and polarization resistance of the battery components are small at high temperatures, so it can operate at a large working current density, improving the specific power of the battery; the electrode activity is high at high temperatures, and there is no need to use precious metal electrodes, reducing battery costs; high temperature operation, high waste heat quality, and the use of high-temperature exhaust gas combined heat and power can significantly improve the overall energy utilization efficiency of the system.
[0003] Traditional SOFCs are mostly supported by ceramics or metal ceramics, which have high material costs, poor mechanical properties, and difficulty in mechanical processing, which seriously restrict the commercialization of SOFCs. With the development of SOFCs towards low temperatures and the rapid development of thin film preparation technology, the SOFC preparation process has been continuously developing towards high efficiency and high level. Using metal materials as the support of SOFCs can not only improve the electrical and thermal conductivity of the anode, effectively reduce the operating temperature of the battery, and achieve rapid battery startup, but also help to improve the structural strength of SOFCs and improve mechanical processing performance, and has a very broad application prospect. Although compared with traditional ceramic-supported SOFCs, metal-supported SOFCs have many advantages such as good mechanical strength, low cost, machinability, low temperature operation, high thermal conductivity, thermal shock resistance, thermal cycle resistance, and rapid startup, the complex preparation process and harsh preparation conditions of metal-supported SOFCs have always been one of the biggest challenges faced by researchers.
[0004] In the prior art, there are mainly two ways to prepare the support body of metal-supported SOFC:
[0005] (1) Stainless steel is used as the support body. For example, the invention patent application entitled "Fuel Cell" published on February 18, 2004 by China Patent Publication No. CN 1476647A and the invention patent application entitled "Anti-seepage sintered ceramic electrolyte layer for solid oxide fuel cell formed on a metal sheet substrate" published on July 13, 2005 by China Patent Publication No. CN 1639895A both use ferritic stainless steel substrate as the plate material, and the support body is prepared by punching. The punching area is 50% to 55% of the central area, and there is no hole at the edge. The hole is a straight hole, which is not conducive to the uniform distribution of gas. Since the hole diameter is required to be very small, about 30 microns, and the hole spacing is uniform, the punching equipment is very demanding. The stainless steel used for the support body is mostly Crofer 22APU plate (SOFC special stainless steel). Crofer 22APU has poor high temperature performance. The maximum manufacturing temperature is limited to about 1000°C, which is lower than the densification temperature of the electrolyte material, resulting in greater technical difficulties in the densification of the electrolyte. In addition, the high cost of Crofer 22APU materials seriously restricts the commercialization of SOFC.
[0006] (2) Using the method mentioned in the invention patent application entitled “A method for preparing a large-size flat-plate metal-supported solid oxide fuel cell” published on January 30, 2013 by China Patent Publication No. CN 102903945A, the metal support layer, the anode layer and the electrolyte layer blanks are prepared by wet casting, and then the metal support half-cell is obtained by stacking and hot pressing. The porous support body is prepared by stainless steel metal powder, and the preparation process of the porous support body is developed, which can also greatly reduce the battery cost. The stainless steel metal powder is directly subjected to the casting high-temperature co-firing technology to prepare a porous stainless steel metal support fuel cell, and the support body is a porous structure with controllable porosity. However, in practical application, this scheme has high requirements on the material of the stainless steel metal powder. For cheap stainless steel metal powder (such as 400 series stainless steel metal powder), the oxidation resistance at high temperature is poor, resulting in its inability to withstand the oxidation caused by the start-stop during long-term use of the battery. The oxidation of the metal support body leads to a significant increase in resistance, and the conductivity deteriorates, which leads to battery failure. Summary of the invention
[0007] The purpose of the present invention is to solve the problem of poor antioxidant performance of the existing solid oxide fuel cell metal support prepared by using cheap stainless steel metal powder, and provide a solid oxide fuel cell metal support and a preparation method thereof. When used, cheap stainless steel metal powder can be used to prepare the metal support, which can not only greatly reduce the manufacturing cost of the support, but also improve the antioxidant ability and electrical conductivity of the metal support.
[0008] The purpose of the present invention is mainly achieved through the following technical solutions:
[0009] A solid oxide fuel cell metal support is composed of 400 series stainless steel metal powder and additives. The additives include nickel, cobalt and molybdenum. Calculated by mass fraction of the total amount of 400 series stainless steel metal powder, the additive contents are as follows: Ni: 0.27% to 0.8%, Co: 0.2% to 0.8%, Mo: 0.2% to 2%.
[0010] Furthermore, the additive also includes any one or more elements of manganese, yttrium, zirconium and copper. Calculated by mass fraction of the total amount of 400 series stainless steel metal powder, the contents of manganese, yttrium, zirconium and copper are as follows: Mn: 0-0.05%, Y: 0-0.4%, Zr: 0-2.6%, Cu: 0-0.5%.
[0011] A method for preparing a metal support for a solid oxide fuel cell comprises the following steps:
[0012] Step S1, preparing a mixed slurry, the mixed slurry formula is as follows:
[0013]
[0014]
[0015] Step S2, tape-casting and drying the slurry obtained in step S1 to obtain a supporting voxel embryo;
[0016] Step S3, cutting the metal support blank obtained in step S2 into a first set size, stacking multiple layers from bottom to top to obtain a set thickness, and then isostatically pressing at 60-85° C. and 40-50 MPa for 5-30 minutes to obtain a composite blank;
[0017] Step S4, after cutting the composite blank into the second set size, degumming for 2 to 6 hours in an air atmosphere at 375 to 600 ° C, and then sintering for 4 to 20 hours at a temperature of 1200 to 1300 ° C to obtain a porous metal support. Among them, the first set size of the present invention is larger than the second set size. The cutting in step S3 of the present invention is usually slightly larger than the target size of the battery. For example, if the target battery size is 7cm*7cm, it will be cut into 8*8cm when cutting in step S3. Because the blank is very thin, there are certain dimensional errors and small edge defects during cutting, which easily lead to the corresponding edges of the battery after lamination are not very neat and have some small defects. Therefore, after isostatic pressing, it is necessary to cut again in step S4 to ensure that there are no obvious defects on the edge of the battery. The present invention performs multi-layer stacking to ensure that the support has a certain thickness and reaches a certain strength. Since the support blank prepared by casting is thin, it is necessary to stack multiple layers together to ensure a certain thickness so that the support reaches a certain strength. When the present invention is implemented, according to the required thickness, that is, according to different usage scenarios of the battery, there are different requirements for battery strength and thickness, and the thickness of the support body can be adjusted to meet the requirement of adjustable battery thickness. The experimental parameter range involved in the present invention is the optimal process parameter range obtained by the inventor after a large number of experiments. For the isostatic pressing temperature, when the temperature is too low, the green body cannot reach a softened state and it is difficult to press under pressure; when the temperature is too high, the residual solvent in the green body will evaporate, affecting the uniformity of lamination. As for the isostatic pressing pressure, if the pressure is too low, it cannot be pressed, and if the pressure is too high, it will increase the process loss of equipment, accessories, etc., and will also affect the density of the green body after lamination, thereby adversely affecting the debinding process. In the specific implementation of the present invention, if the degumming temperature is lower than 375°C, the organic matter added to the support body embryo cannot be completely decomposed during the degumming process, and the decomposition during the subsequent sintering process will produce a large amount of gas, which is easy to cause the support body to crack. If the degumming temperature is higher than 600°C, the metal powder will be severely oxidized in the air atmosphere, which will affect the subsequent sintering and forming of the support body, requiring a higher sintering temperature or not being able to sinter and form at all. In the specific implementation of the present invention, if the sintering temperature is lower than 1200°C, the metal powder cannot be sintered and formed, and is still in powder form without strength. If the temperature is higher than 1300°C, the porosity of the support body will be reduced, and the energy consumption of production will be increased. In addition, if the temperature is higher, the metal powder may even melt.
[0018] Furthermore, in step S1, nickel, cobalt and molybdenum are realized by metal powder or soluble salt or oxide, and when soluble salt or oxide is used, the content of nickel, cobalt and molybdenum is within the mass percentage set in step S1. Among them, nickel, cobalt and molybdenum are used as additives in the preparation of mixed slurry in the present invention, and are specifically prepared by metal powder or soluble salt or oxide. When soluble salt or oxide is used for preparation, the content of nickel, cobalt and molybdenum in the soluble salt or oxide needs to meet the mass percentage requirement set in step S1.
[0019] Furthermore, the mixed slurry formula in step S1 further includes any one or more elements of manganese, yttrium, zirconium, and copper, wherein:
[0020]
[0021] Furthermore, in step S1, manganese, yttrium, zirconium and copper are realized by metal powder or soluble salt or oxide, and when soluble salt or oxide is used, the content of manganese, yttrium, zirconium and copper is within the mass percentage set in step S1. Among them, manganese, yttrium, zirconium and copper are also used as additives when preparing the mixed slurry of the present invention, and are specifically prepared by metal powder or soluble salt or oxide. When soluble salt or oxide is used for preparation, the content of manganese, yttrium, zirconium and copper in the soluble salt or oxide needs to meet the mass percentage requirement set in step S1.
[0022] Furthermore, the pore former is a carbonaceous material.
[0023] Since graphite and activated carbon have small particle sizes, their own properties are compatible with the slurry system of the present invention and will not have a significant impact on the slurry properties. In addition, graphite and activated carbon are widely available, easy to obtain, and cheap. Further, the pore-forming agent uses graphite and / or activated carbon, and the diameter of the carbon powder particles is 200nm to 1μm.
[0024] Furthermore, the sintering in step S4 is carried out in an inert atmosphere or a reducing atmosphere; wherein the inert atmosphere is an argon atmosphere, and the reducing atmosphere is a high-purity hydrogen or a hydrogen-argon mixture. In the specific implementation of the present invention, the support body embryo cannot be sintered in an oxidizing atmosphere containing oxygen, otherwise the metal powder will be oxidized and difficult to sinter and form. Therefore, the present invention can only be sintered in an inert atmosphere or a reducing atmosphere. The reason why the inert atmosphere is argon instead of the more commonly used nitrogen is that nitrogen will react with the metal powder under high temperature conditions to form iron nitride compounds, which hinders the metal powder from further sintering into a metal support body.
[0025] Because 410 stainless steel powder, 430 stainless steel powder and 434 stainless steel powder have better corrosion resistance and oxidation resistance than other 400 series stainless steel powders, the 400 series stainless steel powder is any one of 410 stainless steel powder, 430 stainless steel powder and 434 stainless steel powder.
[0026] In summary, the present invention has the following beneficial effects compared with the prior art: (1) The present invention uses cheap 400 series stainless steel metal powder to prepare a large-sized flat metal support, which can greatly reduce the manufacturing cost of the support, and by adding additives such as nickel, cobalt and molybdenum, the oxidation resistance and electrical conductivity of the 400 series stainless steel metal powder metal support are improved. The metal support prepared by the present invention not only has good flexibility, but also has controllable thickness and porosity of the support, significantly improved oxidation resistance and electrical conductivity, and low cost, which is conducive to large-scale application.
[0027] (2) The present invention adopts a suitable casting formula to obtain a stable 400 series stainless steel metal powder casting slurry, making the casting molding of the 400 series stainless steel metal powder possible, and the obtained casting film has a uniform texture, a certain thickness and strength, and meets the requirements of isostatic pressing of the casting film.
[0028] (3) Compared with the existing metal-supported solid oxide fuel cell technology, the present invention can produce a metal support with high porosity, high conductivity and excellent high-temperature oxidation resistance by adding suitable additives and pore-forming agents, which can improve the performance of the metal-supported battery and extend its service life.
[0029] (4) The raw material cost of the present invention is low, the preparation process is simple, and continuous and batch production can be achieved, which greatly reduces the preparation cost of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0031] Figure 1 This is a physical picture of the large-sized flat metal support prepared in Example 1;
[0032] Figure 2 This is a cross-sectional morphology image (SEM photo) of the large-sized flat metal support prepared in Example 1. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0034] Embodiment 1:
[0035] Add 100g of 430 stainless steel metal powder, 1.02g of nickel oxide, 1.02g of cobalt oxide, 0.079g of manganese dioxide, 2g of molybdenum powder, 0.03g of yttrium oxide, 0.5g of copper oxide, and then add 22g of solvent anhydrous ethanol, 9g of dispersant triethanolamine, 4g of plasticizer acrylic copolymer, 4.5g of binder polyvinyl butyral, and 10g of pore-forming agent graphite into a ball mill; ball mill slurry, and filter and vacuum degas the mixed slurry respectively, and then perform tape casting, and obtain a metal support blank after drying, and cut the blank into a square blank of 8cm×8cm;
[0036] The three layers of metal support blanks are stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 10 minutes, and then cut into 7cm×7cm square blanks. After degumming at 500°C in an air atmosphere for 2 hours, they are sintered at 1200°C in a high-purity hydrogen atmosphere for 20 hours to obtain a metal support embodiment 1 with 430 stainless steel as the main body and auxiliary agents of 0.80% nickel content, 0.80% cobalt content, 0.05% manganese content, 2% molybdenum content, 0.02% yttrium content, and 0.40% copper content. Figure 1 This is a physical picture of the metal support prepared in this embodiment, which has a size of 6cm×6cm. Figure 1 It can be seen that the support prepared in this embodiment has a relatively large size, is silvery white, has a smooth surface, and has no obvious defects.
[0037] Figure 2 The cross-sectional morphology of the support prepared in Example 1 (SEM photo). Figure 2 It can be seen that the metal support body is a porous structure with a thickness of about 400 μm and a porosity of about 18%. The support body has a relatively high porosity.
[0038] Example 2
[0039] Add 100 g of 410 stainless steel metal powder, 1.15 g of nickel acetate tetrahydrate, 0.99 g of cobalt nitrate hexahydrate, and 0.41 g of ammonium molybdate to a ball mill in sequence, then add 18 g of anhydrous ethanol as solvent, 9 g of triethanolamine as dispersant, 4 g of acrylic copolymer as plasticizer, 4.5 g of polyvinyl butyral as binder, and 10 g of activated carbon as pore-forming agent; ball mill slurry, and filter and vacuum degas the mixed slurry, and then perform tape casting, and obtain a metal support blank after drying, and cut the blank into 8 cm×8 cm blanks;
[0040] The three layers of metal support blanks are stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 10 minutes, and then cut into 7cm×7cm square blanks. After degumming at 375°C in an air atmosphere for 6 hours, they are sintered at 1200°C in a high-purity hydrogen atmosphere for 8 hours to obtain a metal support embodiment 2 with 410 stainless steel as the main body, an auxiliary nickel content of 0.27%, a cobalt content of 0.20%, and a molybdenum content of 0.20%.
[0041] Example 3
[0042] Add 100g of 430 stainless steel metal powder, 0.43g of nickel oxide, 0.36g of cobalt oxide, 0.04g of manganese dioxide, 1g of molybdenum powder, 0.03g of yttrium oxide, and then add 22g of solvent anhydrous ethanol, 9g of dispersant triethanolamine, 4g of plasticizer acrylic copolymer, 4.5g of binder polyvinyl butyral, and 15g of pore-forming agent graphite into a ball mill; ball mill slurry, and filter and vacuum degas the mixed slurry respectively, and then perform tape casting, and obtain a metal support blank after drying, and cut the blank into 8cm×8cm blanks;
[0043] The three layers of metal support blanks are stacked from bottom to top, and then statically pressed at 60°C and 50MPa for 20 minutes, and then cut into 7cm×7cm square blanks. After degumming at 375°C in an air atmosphere for 6 hours, they are sintered at 1250°C in a 10% hydrogen-argon mixed gas atmosphere for 8 hours to obtain a metal support embodiment 3 with 430 stainless steel as the main body, auxiliary agents of 0.34% nickel content, 0.28% cobalt content, 0.03% manganese content, 1% molybdenum content, and 0.02% yttrium content.
[0044] Example 4
[0045] Add 100g of 430 stainless steel metal powder, 0.43g of nickel oxide, 0.36g of cobalt oxide, 0.04g of manganese dioxide, 1g of molybdenum powder, 0.4g of yttrium oxide, 2.6g of zirconium dioxide, and then add 24g of solvent anhydrous ethanol, 10g of dispersant triethanolamine, 4.8g of plasticizer acrylic copolymer, 5.4g of binder polyvinyl butyral, and 20g of pore-forming agent graphite into a ball mill; ball mill slurry, and filter and vacuum degas the mixed slurry respectively, and then perform tape casting, and obtain a metal support blank after drying, and cut the blank into 8cm×8cm blanks;
[0046] The three layers of metal support blanks are stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 20 minutes, and then cut into 7cm×7cm square blanks. After degumming at 500°C in an air atmosphere for 2 hours, they are sintered at 1200°C in a high-purity hydrogen atmosphere for 20 hours to obtain a metal support embodiment 4 with 430 stainless steel as the main body and an additive content of 0.34% nickel, 0.28% cobalt, 0.03% manganese, 1% molybdenum, 0.31% yttrium and 1.92% zirconium.
[0047] Example 5
[0048] Add 100g of 430 stainless steel metal powder, 1.02g of nickel oxide, 1.02g of cobalt oxide, 0.079g of manganese dioxide, 2g of molybdenum powder, and then add 24g of solvent anhydrous ethanol, 10g of dispersant triethanolamine, 4.8g of plasticizer acrylic copolymer, 5.4g of binder polyvinyl butyral, and 20g of pore-forming agent graphite into a ball mill; ball mill slurry, and filter and vacuum degas the mixed slurry through a sieve, and then perform tape casting, and obtain a metal support blank after drying, and cut the blank into 8cm×8cm blanks;
[0049] Two layers of metal support blanks are stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 20 minutes, and then cut into 7cm×7cm square blanks. After degumming at 500°C in an air atmosphere for 2 hours, they are sintered at 1200°C for 20 hours in a 10% hydrogen-argon mixed gas atmosphere to obtain a metal support embodiment 5 with 430 stainless steel as the main body, auxiliary nickel content of 0.80%, cobalt content of 0.80%, manganese content of 0.05%, and molybdenum content of 2%.
[0050] Example 6
[0051] Add 100 g of 434 stainless steel metal powder, 0.4 g of nickel oxide, 0.4 g of cobalt oxide, 1 g of molybdenum powder, and then add 20 g of anhydrous ethanol as solvent, 10 g of triethanolamine as dispersant, 4.8 g of acrylic copolymer as plasticizer, 5.4 g of polyvinyl butyral as binder, and 10 g of graphite as pore former into a ball mill; ball mill slurry, filter the mixed slurry through a sieve and vacuum degas, and then perform tape casting, dry to obtain a metal support blank, and cut the blank into 8 cm×8 cm blanks;
[0052] The three layers of metal support blanks are stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 20 minutes, and then cut into 7cm×7cm square blanks. After degumming at 500°C in an air atmosphere for 2 hours, they are sintered at 1250°C in a high-purity hydrogen atmosphere for 20 hours to obtain a metal support embodiment 6 with 434 stainless steel as the main body, auxiliary nickel content of 0.31%, cobalt content of 0.31%, and molybdenum content of 1%.
[0053] Comparative Example 1
[0054] Add 100 g of 430 stainless steel metal powder, 22 g of anhydrous ethanol as solvent, 9 g of triethanolamine as dispersant, 4 g of acrylic copolymer as plasticizer, 4.5 g of polyvinyl butyral as binder, and 10 g of graphite as pore former into a ball mill in sequence; ball mill slurry, filter the mixed slurry through a sieve and perform vacuum degassing, then perform tape casting, and obtain a metal support blank after drying, and cut the blank into 8 cm×8 cm blanks;
[0055] The three layers of metal support blanks were stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 10 minutes, and then cut into 7cm×7cm square blanks. After degumming at 500°C in air atmosphere for 2 hours, they were sintered at 1200°C in high-purity hydrogen atmosphere for 20 hours to obtain 430 stainless steel metal support comparative example 1.
[0056] Comparative Example 2
[0057] Add 100 g of 410 stainless steel metal powder, 0.4 g of yttrium oxide, 18 g of anhydrous ethanol, 9 g of triethanolamine, 4 g of acrylic copolymer, 4.5 g of polyvinyl butyral, and 20 g of activated carbon into a ball mill; ball mill slurry, filter the mixed slurry through a sieve and vacuum degas, and then tape cast. After drying, a metal support blank is obtained, and the blank is cut into 8 cm × 8 cm blanks;
[0058] The three layers of metal support blanks were stacked from bottom to top, and then statically pressed at 70°C and 45MPa for 10 minutes, and then cut into 7cm×7cm square blanks. After degumming at 375°C in an air atmosphere for 6 hours, they were sintered at 1200°C in a high-purity hydrogen atmosphere for 8 hours to obtain a metal support comparative example 2 with 410 stainless steel as the main body and an auxiliary agent yttrium content of 0.31%.
[0059] The porous supports prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6, as well as the porous metal supports prepared in Comparative Examples 1 and 2, were weighed using an analytical balance before and after oxidation at 850°C in an air atmosphere for 2 hours. The weight gain of the supports can be calculated by comparing the mass difference before and after oxidation. The samples with greater weight gain after oxidation have a more serious degree of oxidation. In addition, a four-probe resistivity tester was used to perform a resistivity comparison test on the surface of the metal support after oxidation. Samples with a greater resistivity indicated a more serious degree of oxidation. The test results are summarized in the following table:
[0060] Table 1 Summary of oxidation weight gain rate and resistivity of metal supports in different schemes
[0061]
[0062] According to the data comparison in Table 1, the porous support prepared by the present invention has a smaller mass increase after oxidation than the comparative example 1 without adding an additive and the comparative example 2 with only adding an yttrium oxide additive, and the resistivity is also smaller, indicating that the embodiment schemes of adding oxide combination additives have better antioxidant properties.
[0063] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A solid oxide fuel cell metal support, characterized in that: The invention is composed of 400 series stainless steel metal powder and additives, wherein the additives include nickel, cobalt and molybdenum. Calculated by mass fraction of the total amount of 400 series stainless steel metal powder, the additive contents are as follows: Ni: 0.27%-0.8%, Co: 0.2%-0.8%, Mo: 0.2%-2%.
2. A solid oxide fuel cell metal support according to claim 1, characterized in that: The additive also includes any one or more elements of manganese, yttrium, zirconium and copper. Calculated by mass fraction of the total amount of 400 series stainless steel metal powder, the contents of manganese, yttrium, zirconium and copper are as follows: Mn: 0-0.05%, Y: 0-0.4%, Zr: 0-2.6%, Cu: 0-0.5%.
3. A method for preparing a metal support for a solid oxide fuel cell, characterized in that: The following steps are involved: Step S1, preparing a mixed slurry, the mixed slurry formula is as follows: Step S2, tape-casting and drying the slurry obtained in step S1 to obtain a supporting voxel embryo; Step S3, cutting the metal support blank obtained in step S2 into a first set size, stacking multiple layers from bottom to top to obtain a set thickness, and then isostatically pressing at 60-85° C. and 40-50 MPa for 5-30 minutes to obtain a composite blank; Step S4, after cutting the composite green blank into the second set size, debonding in an air atmosphere at 375-600° C. for 2-6 hours, and then sintering at a temperature of 1200-1300° C. for 4-20 hours to obtain a porous metal support.
4. The method for preparing a metal support for a solid oxide fuel cell according to claim 3, characterized in that: In the step S1, nickel, cobalt and molybdenum are realized by using metal powder or soluble salt or oxide. When soluble salt or oxide is used, the content of nickel, cobalt and molybdenum elements is within the mass parts set in step S1.
5. The method for preparing a metal support for a solid oxide fuel cell according to claim 3, characterized in that: The mixed slurry formula in step S1 further includes any one or more elements of manganese, yttrium, zirconium, and copper, wherein:
6. The method for preparing a metal support for a solid oxide fuel cell according to claim 5, characterized in that: In the step S1, manganese, yttrium, zirconium and copper are realized by using metal powder or soluble salt or oxide. When soluble salt or oxide is used, the content of manganese, yttrium, zirconium and copper elements is within the mass percentage set in step S1.
7. The method for preparing a metal support for a solid oxide fuel cell according to claim 3, characterized in that: The pore former is a carbonaceous material.
8. The method for preparing a metal support for a solid oxide fuel cell according to claim 7, characterized in that: The pore-forming agent is graphite and / or activated carbon, and the diameter of the carbon powder particles is 200nm-1μm.
9. The method for preparing a metal support for a solid oxide fuel cell according to claim 3, characterized in that: In the step S4, the sintering is performed under an inert atmosphere or a reducing atmosphere; wherein the inert atmosphere is an argon atmosphere, and the reducing atmosphere is a high-purity hydrogen atmosphere or a hydrogen-argon mixed gas.
10. The method for preparing a metal support for a solid oxide fuel cell according to claim 3, characterized in that: The 400 series stainless steel metal powder is any one of 410 stainless steel metal powder, 430 stainless steel metal powder and 434 stainless steel metal powder.
Citation Information
Patent Citations
Method for preparing large-size flat plate type metal supporting solid oxide fuel cell
CN102903945A
Fuel cells
CN1476647A
Forming an impermeable sintered ceramic electrolyte layer on a metallic foil substrate for solid oxide fuel cell
CN1639895A